Transformation of Teacher Competencies in Creating Meaningful Learning - Citra Dewi; Sukirdi (CV. Creative Tugu Pena, 2026)
The shifting educational paradigm demands that teachers possess the competencies to create meaningful learning. Transforming teacher competencies is a key factor in facing the challenges of an adaptive, technology-based, and character-building curriculum. This study aims to map teacher competencies in creating meaningful learning based on four main dimensions: pedagogical, professional, social, and personality, as well as identifying strengths and areas that need improvement. A quantitative approach was used with a survey design. The study population was teachers at SDN 16 Bengkulu Selatan. The sample was taken using total sampling, comprising all teachers at the school. The instrument was a Likert-scale questionnaire with 46 statements. Data were analyzed using descriptive statistics to determine the average score for each indicator. The results showed that the majority of indicators were in the good to excellent category, with the highest scores for mastery of learning theory, use of technology, and teacher role models. The lowest scores were found for teacher involvement in village activities and acceptance of peer feedback. Teachers at this school already possess sufficient competencies to create meaningful learning, although social engagement and openness to feedback still require strengthening. These findings form the basis for a more holistic professional development program. This research contributes by integrating four dimensions of teacher competency into a single evaluation framework that can be applied in other schools to comprehensively map the quality of meaningful learning